Work Study Architecture for Lean Waste Analysis to Achieve Optimum Man-Machine Configuration - Abdullah, Rohana; Abd Rahman, Md Nizam (International Journals of Engineering & Sciences, 2014)
To survive in the global marketplace, companies has adopted lean towards reducing wastes and improving their efficiency. Manpower study traditionally employs work study methods such as Process Mapping and Man-Machine Charts which are no longer suitable to be used in the complicated manufacturing environment such as in the electronics manufacturing facility. Thus, a modified work-study architecture is designed and applied at the process under study to optimize the man-machine configuration. This paper details out the development and implementation of the work study architecture to perform lean waste analysis at an electronic manufacturing company. The benefits observed from the implementation phase indicate that the lean waste analysis performed using this system has reduced the lengthy time that work-study usually takes, eliminated human error during analysis and improved the accuracy of data.